Peningkatan Ketahanan Tanaman Pisang Barangan terhadap Blood Disease Bacterium (BDB) dengan Aplikasi Fungi Mikoriza Arbuskular Indigenus - . Suswati; Nasir Najril; . Azwana (Universitas Lampung, 2013)
Increase resistence of barangan banana blood disease bacterium using Indigenus arbuscular mycorhizae fungi. Blood disease caused by Blood disease bacterium (BDB) is the major cause of production loss of banana in Indonesia. There is currently a lack of information about the application of indigenous Arbuscular mycorrhizal fungi (AMF) to increase the Barangan banana resistance to BDB. A greenhouse experiment was conducted to evaluate the increase resistance Barangan banana to 3 (three) types of AMF (Glomus type-1; Acaulospora type-4 and Glomus fasciculatum) and control (without AMF) with 3 replicates. Barangan banana plantlet were inoculated with 50 g fresh AMF inoculants and at 14 days after acclimating have transplanted to soil contaminated BDB. Observation on the Barangan banana seedlings was done after 5-60 days after application included percentage disease, severity disease, incubation periode, BDB population in rhizosfer and AMF percentage root colonization. The result indicated that AMF increased Barangan banana resistance to BDB. Glomus type-1 and G. fasciculatum increased banana resistance by 100% while Acaulospora type-4 takes 66.67% and control none. The disease severity with Acaulospora tipe-4 is 6% lower than controls (32.6%). The highest suppression level was found in 2 isolates of Glomus application was 100% and was followed Acaulospora type-4 is 81.59%. The low intensity of on FMA indigenous treatment applications related to the incubation period and BDB density in rhizosphere of plant roots. The incubation period in mychorized plants has longer 30 dap than controls (10 dap).